Untreated PKU patients without intellectual disability: what do they teach us? - Vliet, Danique van; van Wegberg, Annemiek M.J.; Ahring, Kirsten; Bik-Multanowski, Miroslaw; Casas, Kari; Didycz, Bozena; Djordjevic, Maja; Hertecant, Jozef L.; Leuzzi, Vincenzo; Mathisen, Per; Nardecchia, Francesca; Powell, Kimberly K.; et al. (Nutrients, 2019)
Phenylketonuria (PKU) management is aimed at preventing neurocognitive and psychosocial dysfunction by keeping plasma phenylalanine concentrations within the recommended target range. It can be questioned, however, whether universal plasma phenylalanine target levels would result in optimal neurocognitive outcomes for all patients, as similar plasma phenylalanine concentrations do not seem to have the same consequences to the brain for each PKU individual. To better understand the inter-individual differences in brain vulnerability to high plasma phenylalanine concentrations, we aimed to identify untreated and/or late-diagnosed PKU patients with near-normal outcome, despite high plasma phenylalanine concentrations, who are still alive. In total, we identified 16 such cases. While intellectual functioning in these patients was relatively unaffected, they often did present other neurological, psychological, and behavioral problems. Thereby, these “unusual” PKU patients show that the classical symptomatology of untreated or late-treated PKU may have to be rewritten. Moreover, these cases show that a lack of intellectual dysfunction despite high plasma phenylalanine concentrations does not necessarily imply that these high phenylalanine concentrations have not been toxic to the brain. Also, these cases may suggest that different mechanisms are involved in PKU pathophysiology, of which the relative importance seems to differ between patients and possibly also with increasing age. Further research should aim to better distinguish PKU patients with respect to their cerebral effects to high plasma phenylalanine concentrations.